2019
DOI: 10.1093/eurpub/ckz186.048
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to enhance follow-up response in a cohort study with Berliners of Turkish descent

Abstract: Background Follow-up participation and retention are essential in long-term cohort studies. Loss to follow up may reduce the power of statistical analyses and external validity. The aim of this analysis was to evaluate the response after different contact methods in a cohort study with Berliners of Turkish descent and to compare characteristics of participants with those of non-participants. Methods In 2012-2013, Berliners wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Participants were asked about health status and behavior, health care utilization, among other questions. A description of the follow-up recruitment has been provided by Krist et al [ 26 ]. The 3rd assessment (2nd follow-up) took place during the COVID-19 pandemic between July and December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked about health status and behavior, health care utilization, among other questions. A description of the follow-up recruitment has been provided by Krist et al [ 26 ]. The 3rd assessment (2nd follow-up) took place during the COVID-19 pandemic between July and December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that re-participation at 6-year follow-up could be increased via home visits by 9.5% (from 40.6% after postal invitation and two reminders to 50.1%). Participants recruited via home visits were more often women, had more often their own migration experience, lower education, or were unemployed compared to the participants recruited via mailing and telephone contact [ 40 ]. However, when comparing our data with census data assessed in 2011 via the German “Mikrozensus 2011”, even if home visits among the Turkish sample led to the participation of less-educated persons, participants were still different from the underlying migrant population in Berlin.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline and follow-up recruitment were conducted using bilingual written invitations, telephone contacts, and home visits performed by bilingual study staff. A description of the follow-up recruitment and retention methods was published by Krist et al [ 40 ]. The study was approved by the ethical review committee of the Charité—Universitätsmedizin Berlin (EA1/206/17), Germany, and registered at the German Clinical Trials Register under the registration number DRKS00013545.…”
Section: Methodsmentioning
confidence: 99%